Oral anticoagulation, stroke and thromboembolism in patients with atrial fibrillation and valve bioprosthesis - Philippart, Raphael; Brunet-Bernard, Anne; Clementy, Nicolas; Bourguignon, Thierry; Mirza, Alain; Angoulvant, Denis; Babuty, Dominique; Lip, Gregory Y. H.; Fauchier, Laurent (Thrombosis and Haemostasis, 2016)
Vitamin K antagonists are currently recommended in patients with ‘valvular’ atrial fibrillation (AF), e. g. those having mitral stenosis or artificial heart valves. We compared thromboembolic risk in patients with ‘non valvular’ AF and in those with AF and biological valve replacement (valve bioprosthesis). Among 8962 AF patients seen between 2000 and 2010, a diagnosis of ‘non-valvular AF’ was found in 8053 (94 %). Among patients with ‘valvular’ AF, 549 (6 %) had a biological prosthesis. The patients with bioprosthesis were older and had a higher CHA2DS2-VASc score than those with non valvular AF. After a follow-up of 876 é 1048 days (median 400 days, interquartile range 12–1483), the occurrence of thromboembolic events was similar in AF patients with bioprosthesis compared to those with ‘non valvular’ AF (hazard ratio [HR] 1.10 95 % confidence interval [CI] 0.83–1.45, p=0.52, adjusted HR 0.93, 95 %CI 0.68–1.25, p=0.61). Factors independently associated with increased risk of stroke/TE events were older age (HR 1.25, 95 %CI 1.16–1.34 per 10-year increase, p> 0.0001) and higher CHA2DS2-VASc score (HR 1.35, 95 %CI 1.24–1.46, p> 0.0001) whilst female gender (HR 0.75, 95 %CI 0.62–0.90, p=0.002), use of vitamin K antagonist (HR 0.83, 95 %CI 0.71–0.98, p=0.03) were independently associated with a lower risk of stroke/TE. Neither the presence of bioprosthesis nor the location of bioprosthesis was independent predictor for TE events. In conclusion, AF patients with bioprosthesis had a non-significantly higher risk of stroke/TE events compared to patients with non-valvular AF. Second, the CHA2DS2-VASc score was independently associated with an increased risk of TE events, and was a valuable determinant of TE risk both in AF patients with non-valvular AF as well as those with bioprosthesis, whether treated or not treated with OAC.Note: The review process for this paper was fully handled by Christian Weber, Editor in Chief.
Keywords: Atrial fibrillation; ischaemic stroke; biological valve prosthesis